Innate Lymphoid Cells in Mucosal Immunity - Panda, Santosh K.; Colonna, Marco (Frontiers in Immunology, 2019)
Innate lymphoid cells (ILCs) are innate counterpart of T cells that contribute to immune responses by secreting effector cytokines and regulating the functions of other innate and adaptive immune cells. ILCs carry out some unique functions but share some tasks with T cells. ILCs are present in lymphoid and non-lymphoid organs, and are particularly abundant at the mucosal barriers, where they are exposed to allergens, commensal microbes and pathogens. The impact of ILCs in mucosal immune responses has been extensively investigated in the gastrointestinal and respiratory tracts, as well as in the oral cavity. Here we review the state-of-the-art knowledge of ILC functions in infections, allergy and autoimmune disorders of the mucosal barriers.